THE STUDY OF INSTILLING PLURALITY VALUES TO THE STUDENTS OF ISLAMIC SCHOOLS IN MAKASSAR (JOURNAL OF INDONESIAN ISLAM, 2012)
This study tries to discuss the central issue of the instilling plural values to learners of each level of Islamic schools in Makassar. This study focuses on Islamic schools, since the teaching of religious subjects were also offered at public schools. In order to limiting the scope of the research, this study highlights on the extent of religious teaching and how the teaching are synchronized with of the plurality values  in schools that consists of diverse ethnicity and culture in one hand, and diverse religious beliefs outside the schools, in another hand. The main problem statement is how the plurality values are instilled at Islamic schools in Makassar. The instilling process of plural values is tilled at Islamic schools in Makassar. The instilling process of plural values and culture is qualitative with socio-cultural pedagogical approach. The finding is that the instilling of the plurality values had been implemented but is not yet an adequate process, because it is still sporadic. Also, it is not yet concretely reflected in the curriculum.